Comparison Analysis Of Cost And Time In Situ Concrete Implementation Method With Pre Cast - Andrew Samuel Erionkita Purba (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2020)
In the implementation of construction projects, there are several methods of concrete implementation used, such as in situ concrete which is carried out in the implementation of casting at the project site so that it takes a long time and quite a lot of formwork. In addition, there is also a method of implementing pre-cast concrete which is basically the same as conventional concrete, but the production process is carried out in a special place for pre-cast production and then brought to the project site and installed into concrete to form a unified structure. So it doesn't take too long and is considered more efficient. This study aims to compare the cost and time of implementing in situ and pre-cast concrete methods on one of the bridge abutments of the Kuala Tanjung Multi Purpose Terminal Project using the data obtained in the form of image data, material prices, wages and equipment. And from the results of the calculation analysis, the results of the method of implementing concrete on one of the bridge abutments are that with in situ concrete it takes 7 days to implement with a total cost of Rp. 807,867,550, - and with pre cast concrete it takes 5 days to implement total cost Rp.612,345,190,-. So from this study, it was found that the comparison method for the implementation of pre-cast concrete was more efficient with a cheaper price comparison of Rp. 195.552.360, - and 2 days faster time for the work of one bridge abutment.